The international monetary system : an essay in interpretation - Hoffmeyer, Erik, 1924- (North-Holland, 1992)
This book interprets the historical evolution of how and why the international monetary system has been transformed. The strategies of the major decision-makers are defined and described, and an analysis made of how these strategies were adapted. The structure of the analysis differs from other such contributions, in that it does not concentrate on the way in which disturbances have developed, but rather on describing the pattern of reaction of policy makers to disturbances, and in particular on the political element in the decisions. This structure of analysis makes relevance criteria somewhat different from most academic literature on the international monetary system. A substantial amount of evidence is presented that has hitherto been largely neglected by experts; for example the sterling support schemes, the gold pool transactions, the use of the swap network, Schiller's preparation of the German block floating, the intervention pattern among key currencies, and the views arising from the minutes of the Federal Open Market Committee. In order to facilitate comparison with other presentations careful documentation is provided of the points made. Apart from the literature referred to in the Bibliography, all material used - comprising documents, memoranda, publications and communiqu & eacute;s - has been organized in a computer index containing about 500 entries. Background material covered by one or more of these entries is available to the interested reader.